Study of the effect of organic shell on the leaching of protective compositions from wood protected from fire - TSAPKO, Yuriy; TSAPKO, Aleksii; BONDARENKO, Olga; LIALINA, Natalia; ANOPKO, Dmitriy; YUSHCHENKO, Alina (Ways to Improve Construction Efficiency, 2024)
Today, there are various ways to fireproof wood. When wood is moistened, flame-retardants dissolve in a humid environment and gradually wash out to the surface, after which the fire protection effect decreases over time. Acid-based products do not have a significant leaching problem due to changes in wood moisture, but by penetrating deep into the wood structure and interacting with cellulose, they reduce strength characteristics. Another method is to apply a coating based on organic or inorganic binders to the wood surface. Products based on organic binders have increased smoke generation and toxic substances, so their use is dangerous. Therefore, an analysis of protective materials for wooden building structures was carried out and the need to develop reliable methods for studying the leaching of flame-retardants necessary for the creation of new types of fire protection materials was established. There is a need to determine the conditions for the formation of a barrier to the leaching of flame-retardants and to establish a mechanism for inhibiting the transfer of moisture to the material. In this regard, a mathematical model of the process of leaching protective substances from wood after its impregnation with flame-retardants when using a polymeric shell made of organic material as a coating was developed, which allows us to evaluate the effectiveness of the polymeric shell by the amount of water absorbed. The results of calculating the weight gain of the sample during exposure to water indicate an ambiguous effect of the nature of the protection on water absorption. In particular, this implies the availability of data sufficient for the qualitative process of inhibiting moisture diffusion and identifying, on its basis, the time point from which the decrease in coating efficiency begins. Thus, there is reason to believe that it is possible to regulate the processes of wood protection in a targeted manner by using polymer coatings that can form a protective layer on the surface of the material that inhibits the rate of water absorption.